Distal Corporal Anchoring Stitch: A Technique to Address Distal Corporal Crossovers and Impending Lateral Extrusions of a Penile Prosthesis. Issue 6 (1st June 2017) - Antonini, Gabriele; Busetto, Gian Maria; Del Giudice, Francesco; Ferro, Matteo; Chung, Benjamin I.; Conti, Simon L.; Suarez Sarmiento, Alfredo; Pacchiarotti, Arianna; De Berardinis, Ettore; Perito, Paul E.
Abstract: Background: Unidentified distal crossovers, delayed distal crossovers, and impending lateral extrusion are complications of penile prosthesis implant insertion but are not as common as prosthesis infection or mechanical failure. Aim: To evaluate results of a surgical technique, the distal corporal anchoring stitch, that addresses fixation of the penile prosthesis in patients with these complications. Methods: A lateral sub-coronal incision is used on the side where the crossover or laterally extruding cylinder should be positioned. Dissection is carried through the Buck fascia, followed by a transverse incision of the tunica albuginea, where the distal aspect of the affected cylinder is delivered. A 4-0 PDS suture is threaded through the distal cylinder ring of the implant. A new, properly positioned intracorporal channel is created and the suture is passed through the distal end of the channel. Once the suture is through the glans and the cylinder is in the correct position, a small cruciate incision is made on the glans at the location of the anchor stitch. The suture is tied with the knot buried in the glans tissue. Outcomes: Fifty-three patients underwent treatment of their distal penile implant crossover with a distal corporoplasty using this method and their anatomic and functional outcomes and overall satisfaction were evaluated. Results: This technique ensured that the cylinder remained in the newly created, appropriately positioned channel. No patients developed infections, wound-healing defect, glandular hypoesthesia, anesthesia, or altered sensation or pain in the glans related to the suture and only two reported recurrence of a lateral herniation that did not require further treatment. Clinical Implications: Distal fixation of the penile prosthesis is a useful surgical adjunct to treating patients with prosthetic lateral extrusions or crossovers that can be applied in almost all cases. Strengths and Limitations: Considering these rare complications, our experience is based on a relatively large number of patients and showed a low incidence of complications and a high satisfaction rate. The main limitation of this study is the retrospective nature of the data and the series included patients from two high-volume surgeons that might not be generalizable to all practices. Conclusion: The distal corporal anchoring stitch is safe and effective in securing distal fixation of the extruding inflatable penile prosthesis.